Hubungan Terpaan Peringatan Risiko Bahaya Merokok pada Kemasan Rokok dan Intensitas Komunikasi Peer Group dengan Minat Berhenti Merokok Perempuan - Indah Nur Masita; Hedi Pudjo Santosa (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
This research is based on the increase of female active smokers in Indonesia. The increase does not spare from the way of advertising, promotion, sponsorship, CSR, cross-border advertising, and display on cigarette packaging (TCSC, 2018: 2). Therefore, the Government tried to minimize the number of smokers with regulatory efforts on cigarette advertisements. One of them with Pictorial Health Warning ads as an illustrated health warning on cigarette packaging. This research aims to know the correlation between advertisement exposure from the risk of smoking hazard on cigarette packaging and intensity of peer group communication with women’s interest in quitting smoking. The technique used accidental sampling with a total sample of 50 respondents. The finding of this study indicates that there is a positive effect between exposure to the risk of smoking hazard on cigarette packages with women’s interest in quitting smoking, with a strong correlation using Cognitive Response Theory. The result showed that the higher the exposure to the risk of smoking hazard on cigarette packaging, the higher the women will have the urge or interest to quit smoking. The second finding shows that there is a positive effect between the intensity of peer group communication with women’s interest in quitting smoking, with a strong correlation using the Reference Group Theory. This result means that the higher the intensity of peer group communication, the higher the women will have the urge or interest in quitting smoking